Barriers to a software reminder system for risk assessment of stroke in atrial fibrillation: a process evaluation of a cluster randomised trial in general practice - Holt, T; Dalton, A; Kirkpatrick, S; Hislop, J; Marshall, T; Fay, M; Qureshi, N; Lasserson, D; Kearley, K; Mollison, J; Yu, L; Fitzmaurice, D; et al. (Royal College of General Practitioners, 2018)
BACKGROUND:Oral anticoagulants reduce the risk of stroke in patients with atrial fibrillation (AF), but are underused. AURAS-AF (AUtomated Risk Assessment for Stroke in AF) is a software tool designed to identify eligible patients and promote discussions within consultations about initiating anticoagulants. AIM:To investigate the implementation of the software in UK general practice. DESIGN AND SETTING:Process evaluation involving 23 practices randomly allocated to use AURAS-AF during a cluster randomised trial. METHOD:An initial invitation to discuss anticoagulation was followed by screen reminders appearing during consultations until a decision had been made. The reminders required responses, giving reasons for cases where an anticoagulant was not initiated. Qualitative interviews with clinicians and patients explored acceptability and usability. RESULTS:In a sample of 476 patients eligible for the invitation letter, only 159 (33.4%) were considered suitable for invitation by their GPs. Reasons given were frequently based on frailty, and risk of falls or haemorrhage. Of those invited, 35 (22%) started an anticoagulant (7.4% of those originally identified). A total of 1695 main-screen reminders occurred in 940 patients. In 883 instances, the decision was taken not to initiate and a range of reasons offered. Interviews with 15 patients and seven clinicians indicated that the intervention was acceptable, though the issue of disruptive screen reminders was raised. CONCLUSION:Automated risk assessment for stroke in atrial fibrillation and prompting during consultations are feasible and generally acceptable, but did not overcome concerns about frailty and risk of haemorrhage as barriers to anticoagulant uptake.